Rivelare la verità della guerra.: La fine di San Pietroburgo di Vsevolod Illarionovič Pudovkin (PHILM. Rivista di filosofia e cinema, 2024)
In the first decades of the last century, cinema as a new mechanical art seemed logically capable of representing the new war that broke out in 1914, the “war of materials”. Actually, even the cinema cannot show this war. However, during the war itself, devised a novel cinematic technique, known as montage, which would prove to be a significant innovation in the field. The film montage technique was not employed with the intention of representing the war; rather, it was used to reveal its inherent truth, which could not be conveyed through traditional cinematic means due to the unrepresentability of the new war. This paper attempts to show how the use of “parallel montage” in Pudovkin’s The End of St. Peters- burg serves to clarify the fundamental nature of war.